Post-Traumatic Growth Following the Experience of Interpersonal Violence: The Roles of Perceived Stigma and Social Support - Wellington Olubukola (GENEROS: Multidisciplinary Journal of Gender Studies (Hipatia Press), 2023)
Post-Traumatic Growth is a term that refers to an individual's experience of considerable positive transformation following the occurrence of a traumatic event. This growth may be rapid, gradual, or non-existent, depending on the circumstances (such as social support or societal stigma) to which the victims are subjected during the process. However, the high prevalence of trauma among traumatized victims and the benefits of post-traumatic growth (PTG) discovered in increasing empirical research demonstrate the need of fostering PTG in victims of interpersonal violence. As a result, the current study analysed risk variables for PTG development. The study enrolled 200 women and men recruited through an organization that provides services to trauma victims. The data were gathered via an online survey that included the PTG inventory and an information sheet on demographic, social support, and stigma-related characteristics. Social stigma and support were found to be significant predictors of PTG, with stigma being associated with lower PTG and family and religious support being associated with higher PTG. The limitations and policy implications were highlighted, and recommendations for additional research were presented.